Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445243
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Analysis of Multitasking Behavior During Remote Meetings

Abstract: Virtual meetings are critical for remote work because of the need for synchronous collaboration in the absence of in-person interactions. In-meeting multitasking is closely linked to people's productivity and wellbeing. However, we currently have limited understanding of multitasking in remote meetings and its potential impact. In this paper, we present what we believe is the most comprehensive study of remote meeting multitasking behavior through an analysis of a large-scale telemetry dataset collected from F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 54 publications
1
49
0
1
Order By: Relevance
“…Participants also noted that turning one's video on or off was a crucial signal of engagement, with camera on signaling high engagement and camera off indicating low engagement. Cao et al (2021) found multitasking to be a common behavior in videoconference meetings, with about 30% of meetings involving email multitasking. Many participants (32%) noted they were more likely to multitask when the video camera and microphone were turned off.…”
Section: Use Of Videoconferencing For Workplace Meetingsmentioning
confidence: 99%
“…Participants also noted that turning one's video on or off was a crucial signal of engagement, with camera on signaling high engagement and camera off indicating low engagement. Cao et al (2021) found multitasking to be a common behavior in videoconference meetings, with about 30% of meetings involving email multitasking. Many participants (32%) noted they were more likely to multitask when the video camera and microphone were turned off.…”
Section: Use Of Videoconferencing For Workplace Meetingsmentioning
confidence: 99%
“…While task effectiveness, trust, or other values have been compared and contrasted in videoconferencing against other modalities [8,16,45], comparisons of video meetings with and without parallel chat are not available. In work contexts, video-meeting research on attention and multi-tasking has noted parallel chat as one among many distractions [11,34,41], but not provided detail.…”
Section: Prior Workmentioning
confidence: 99%
“…Interestingly, a virtual classroom opens up the scope for multitasking [10,12,13,32], where a student may perform several other activities while still attending the classes online. These activities range from productive activities that support interaction with the classroom during the live lecture (like taking notes, browsing related concepts on the web, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In both the above cases, the eyes of a student might not be focused on the computer's screen; a method that solely analyzes eye dynamics to infer students' engagement may result in false positives when the student performs productive multitasking. Understanding students' attention in the presence of multitasking is challenging, as a student might get involved with such activities for a significant duration during a live class [12]. Apart from that, gazing at the screen is not an essential condition for getting involved in an online meeting [19,20].…”
Section: Introductionmentioning
confidence: 99%